Perceptions and Technological Addictions in Adults of Different Generations. (Revista de Psicología, 2025)
Although research often focuses on adolescents, the relationship with Information and Communication Technologies represents a risk factor for the general population, including the ways in which adults perceive technological addictions. A cross-sectional descriptive study was conducted with users of various technologies (aged 25–59, from Córdoba, Argentina); perceptions and social judgments regarding the non-instrumental use of Information and Communication Technologies were analyzed, comparing Generations X and Y. Both generations perceive the non instrumental use of Information and Communication Technologies as spontaneous and sometimes excessive; Generation Y perceives such use as safe, beneficial, interesting, and socially engaging. The differences between participant’s perceptions and current mental health criteria regarding video games and smartphones constitute a factor of stigmatization.
Keywords: Technological Addiction; Social judgement; Technological generations; Perceptions; Adults